DETERMINANTS OF TOURIST REVISIT INTENTION TO KOTA BATU - Merzelinda Fairuz Ramadlani; Djumilah Hadiwidjaja (Jurnal Ilmiah Mahasiswa FEB, 2012)
This research is aimed at understanding what factors make the tourists satisfied and have revisit intention to a tourism destination, specifically Kota Batu. There are five determinants of revisit intention in this study, perceived attractiveness, perceived quality, perceived value, perceived risk, and satisfaction. This research is an explanatory research, based on the fact that the purpose of this study is to explain the relation and the influence of some pre-determined variables. Method used in gathering data is questionnaire with a random 100 sample of tourist in Kota Batu selected by non probability sampling. To analyze the data, a path analysis and classical assumption (i.e. normality and linearity) are used. The result of this study indicates that perceived attractiveness, perceived quality and perceived value significantly affect the tourist revisit intention only when the tourist are satisfied. Satisfaction in the consumer perception (attractiveness, quality, value and risk) influences and enhances the tourist revisit intention. This study also shows that the tourists feel highly attracted, consider the holiday to be high quality, a good value and a satisfactory experience. They also have quite a high intention to visit Kota Batu again in the future. Although they also consider Kota Batu to have a high risk, the perceived risk does not significantly influence satisfaction and revisit intention. Keywords : tourism, tourist destination, consumer behavior, consumer perception, return visit intention, maketing strategy.